2006
DOI: 10.1021/la061088i
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Nonionic Copolymer-Functionalized Laponite Clay. A Thermodynamic and Spectrophotometric Study To Characterize Its Behavior toward an Organic Material

Abstract: The affinity of functionalized Laponite clay toward an organic material in the aqueous phase was explored. Functionalization was performed by using triblock copolymers based on ethylene oxide (EO) and propylene oxide (PO) units that are EO(11)PO(16)EO(11) (L35) and PO(8)EO(23)PO(8) (10R5). Phenol (PhOH) was chosen as organic compound, which represents a contaminant prototype. To this purpose, densities and enthalpies of mixing as well as PhOH UV-absorption spectra were determined. The enthalpy and the spectrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The X-ray diffraction data of the nanocomposites indicated an exfoliated structure. Finally, De Lisi et al also investigated the affinity toward an organic material, phenol, of the modified Laponite ® with PEO-PPO-PEO triblock copolymers [172]. The authors observed that the addition of copolymers to a phenol/Laponite ® solution led to the replacement of the organic material by the PEO-PPO-PEO.…”
Section: Polymer/clay Nanocompositesmentioning
confidence: 99%
“…The X-ray diffraction data of the nanocomposites indicated an exfoliated structure. Finally, De Lisi et al also investigated the affinity toward an organic material, phenol, of the modified Laponite ® with PEO-PPO-PEO triblock copolymers [172]. The authors observed that the addition of copolymers to a phenol/Laponite ® solution led to the replacement of the organic material by the PEO-PPO-PEO.…”
Section: Polymer/clay Nanocompositesmentioning
confidence: 99%
“…Several studies have been devoted to the physico-chemical characterization of aqueous nanoclay dispersions in the presence of adsorbing species. [13][14][15][16] Laponite RD is a synthetic clay that forms charge-stabilized colloidal dispersion in water. 17 The net charge of a single particle is negative and it is due to the negatively charged faces and slightly positive edge.…”
Section: Introductionmentioning
confidence: 99%
“…17. The clay Laponite XLG 22 was purchased from Rockwood Clay Additives GmbH, Moosburg. Polydimethylsiloxane (PDMS) was purchased from Shinetsu Kagaku, Tokyo.…”
Section: Introductionmentioning
confidence: 99%